Principal Leadership Strategy in Optimizing Human Resource Management to Improve the Quality of Elementary Schools in Cluster I Trumon Tengah, South Aceh in the Digital Era - Misdarwati Misdarwati; Bansu Irianto Ansari; Muhammad Iqbal (FKIP - Universitas Riau, 2026)
This study aims to analyze the leadership strategies of school principals in optimizing human resource management to improve the quality of education in the digital era. The research method used is a qualitative approach with a descriptive research type. The sample of this study consisted of 20 respondents. The study was conducted at Krueng Batee Public Elementary School and Ie Jeureuneh Public Elementary School UPT IV located in Cluster I Trumon Tengah, South Aceh Regency. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. Data analysis techniques used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that participatory leadership increases teacher involvement and responsibility, while transformational leadership strengthens motivation and awareness of innovation and technological adaptation. Teachers' digital competence is in the developing category and the digitalization of human resource management has not been optimally integrated. Adaptive principal leadership, supported by the development of digital competence and technology-based management systems, plays an important role in improving the quality of education in the digital era.